Key geological factors controlling oil displacement efficiency of CO injection in low-permeability reservoirs - Zhaosheng Wang; Lianbo Zeng; Jiangtao Yu; Zhenguo Zhang; Siyu Yang; Yuncheng Liu (Energy Exploration & Exploitation, 2021)
Carbon dioxide (CO 2 ) flooding is an effective method to enhance oil recovery in low-permeability reservoirs. Studying key geological factors controlling oil displacement efficiency is of great significance to the CO 2 injection scheme design in low-permeability reservoirs. Focusing on low-permeable H reservoir in Songliao Basin, China, this paper describes the contact and connection of sand bodies, natural fractures and high-permeability zones with core samples, log data and experiment firstly. After that, the impact of interaction of sand body connection, natural fracture and high-permeability zone on oil displacement efficiency is determined by using geological and dynamic data in CO 2 injection area. Results indicate that the connection of single sand bodies between injectors and producters wells primarily controls CO 2 flooding in low-permeability reservoirs. Furthermore, coupling of sand body connection, natural fractures and high-permeability zones is the key geological factor governing oil displacement efficiency of CO 2 injection in low-permeability reservoirs, where well or generally-connected sand bodies can improve the efficiency significantly. Meanwhile, the dominant seepage channels in other directions have no influence on producers, which is beneficial to improve CO 2 flooding efficiency.